Ovarian Steroids Mediate Sex Differences in Alcohol Reward After Brain Injury in Mice - Oliverio, Robin; Fitzgerald, Julie; Velazquez-Cruz, Ruth; Whitehead, Bailey; Karelina, Kate; Weil, Zachary M. (Frontiers in Behavioral Neuroscience, 2022)
Intoxication is a leading risk factor for injury and TBI increases the risk for later alcohol misuse, especially when the injury is sustained in childhood. Previously, we modeled this pattern in mice, wherein females injured at postnatal day 21 drank significantly more than uninjured females, while we did not see this effect in males. However, the biological underpinnings of this sex difference have remained elusive. In this study, we utilize this preclinical model and traditional endocrine manipulations to assess the effect of perinatal sex steroids on post-injury ethanol response. We found that perinatal androgen administration and adult ovariectomy prevented the development of conditioned place preference to ethanol in females, while there was not an effect of endocrine manipulation on injury severity as measured through axonal degeneration. Finally, although injury affected the amount of microglia in males, there was no corresponding effect of endocrine manipulations, which suggests that males exhibit prolonged neuroinflammation, but sex steroids are not involved in the mechanism. These results, therefore, indicate that ovarian sex steroids are involved in the mechanism by which females develop greater alcohol preference after a juvenile TBI.